A Comparison of Owner-Assessed Long-Term Outcome of Arthroscopic Intervention versus Conservative Managemento f Dogs with Medial Coronoid Process Disease - Dempsey, Lara M.; Maddox, Thomas W.; Comerford, Eithne J.; Pettitt, Rob A.; Tomlinson, Andrew W. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives The purpose of this study was to compare the long-term outcome of dogs with medial coronoid process disease (MCPD) treated with arthroscopic intervention versus conservative management.Materials and Methods Medical records of dogs with MCPD treated by arthroscopic intervention or conservative management over an 8-year period were retrospectively reviewed. Long-term outcome (>12 months) was assessed via owner questionnaire including Liverpool Osteoarthritis in Dogs (LOAD) scores and Canine Brief Pain Inventory scores.Results Data from 67 clinically affected elbow joints (67 dogs) diagnosed with MCPD on computed tomography were included. Forty-four dogs underwent arthroscopic intervention and 23 dogs were treated with conservative management. The median LOAD and Pain Severity Score (PSS) for dogs in the arthroscopic intervention group compared with the conservatively managed group were not significantly different (p = 0.066 and p = 0.10, respectively). The median Pain Interference Score (PIS) was significantly higher in the arthroscopic intervention group versus the conservative management group (p = 0.028). There was no significant difference after controlling for age. For LOAD, PSS and PIS, older age at diagnosis was all significantly associated with higher scores (p = 0.048, p = 0.026 and p = 0.046, respectively) and older age at time of questionnaire completion showed a stronger association with the scores (p ≤0.001 for all).Clinical Significance Arthroscopic intervention showed no long-term benefit over conservative management for dogs with MCPD.
Keywords: medial coronoid process disease; dogs; arthroscopy; conservative management; clinical metrology instrument